Integrin α5β1, as a Receptor of Fibronectin, Binds the FbaA Protein of Group A Streptococcus To Initiate Autophagy during Infection - Jiachao Wang (American Society for Microbiology, 2020)
ABSTRACT Group A Streptococcus (GAS), one of the most common extracellular pathogens, has been reported to invade epithelial and endothelial cells. Our results reveal that M1 GAS strain SF370 can be effectively eliminated by respiratory epithelial cells. Emerging evidence indicates that autophagy is an important strategy for nonphagocytes to eliminate intracellular bacteria. Upon pathogen recognition, cell surface receptors can directly trigger autophagy, which is a critical step in controlling infection. However, the mechanisms of how cells sense invading bacteria and use this information specifically to trigger autophagy remain unclear. In this study, we stimulated cells and infected mice with M and FbaA mutants of M1 GAS strain SF370 or with purified M and FbaA proteins (two critical surface structural proteins of GAS), and found that only FbaA protein was involved in autophagy induction. Furthermore, the FbaA protein induced autophagy independent of common pattern recognition receptors (such as Toll-like receptors); rather, it relies on binding to integrin α5β1 expressed on the cell surface, which is mediated by extracellular matrix protein fibronectin (Fn). The FbaA-Fn-integrin α5β1 complex activates Beclin-1 through the mTOR-ULK1–Beclin-1 pathway, which enables the Beclin-1/Vps34 complex to recruit Rab7 and, ultimately, to promote the formation of autophagosomes. By knocking down integrin α5β1, Fn, Atg5, Beclin-1, and ULK1 in Hep2 cells and deleting Atg5 or integrin α5β1 in mice, we reveal a novel role for integrin α5β1 in inducing autophagy. Our study demonstrates that integrin α5β1, through interacting with pathogen components, initiates effective host innate immunity against invading intracellular pathogens. IMPORTANCE Autophagy is generally considered a strategy used by the innate immune system to eliminate invasive pathogens through capturing and transferring them to lysosomes. Currently, researchers pay more attention to how virulence factors secreted by GAS regulate the autophagic process. Here, we provide the first evidence that the structural protein FbaA of M1 GAS strain SF370 is a potent inducer of autophagy in epithelial cells. Furthermore, we demonstrate that integrin α5β1 in epithelial cells in vitro and in vivo acts as a receptor to initiate the signaling for inducing autophagy by binding to FbaA of M1 GAS strain SF370 via Fn. Our study reveals the underlying mechanisms by which pathogens induce Fn-integrin α5β1 to trigger autophagy in a conserved pattern in epithelial cells.